Late Achaemenid and Early Hellenistic Pisidian Material Culture from Düzen Tepe (SW Anatolia) - Daems, D; Braekmans, Dennis; Poblome, J (University of Leuven, 2017)
The continued importance of pottery studies for the development of the archaeological discipline can hardly be overstated. In this paper we discuss the pottery found at the settlement at Düzen Tepe (SW Anatolia), following the template of the well-established typological and fabric identification practices developed by the Sagalassos Archaeological Research Project for the Sagalassos Red Slip Ware production from Roman imperial times. A newly devised typology of the late Achaemenid to early Hellenistic (5th to 2nd centuries BCE) material of Düzen Tepe is presented. Comparisons with parallels in pottery material indicate that this material was firmly embedded in a (southwestern) Anatolian framework, generally matching a chronological window from the fourth to third centuries BCE.